Production of Seasoning “Mirin” from Thai Rice by Fermentation - Werasit Kanlayakrit; Metinee Maweang (Agriculture and Natural Resources, 2006)
The investigation of the use of Aspergillus oryzae strain and Thai non-glutinous rice varieties, which are suitable for enzyme production for koji preparation was carried out. A. oryzae strain no. WM-2 could produce a-amylase enzyme at the highest level while “Leung 11”, a non-glutinous rice variety was the most suitable for koji preparation because of its unaggregation characteristics which are good for enzyme production (31.71 units/ml of α-amylase and 6.66 units/ml of acid protease). The suitable ratio of solid:liquid content for mirin production was also studied and it was found that the ratio of 60:40 was the most appropriate because it gave rather pale color and suitable residual alcohol concentration (13 % v/v). This ratio was subsequently used for the determination of an appropriate ratio of koji to glutinous rice. The result indicated that the ratio of koji to glutinous rice of 1:7 gave good quality mirin when comparing with the commercial mirin. Based on the scaling-up of koji preparation, it was found that the cultivation time of 36 h gave the highest activities of α–amylase and protease, which are suitable for mirin production. Ten kilograms of rice koji with 1.0 inch bed thickness gave suitable conditions for enzyme production (322.0 units/g dry wt. of a–amylase and 150.82 units/g dry wt. of acid protease). The results from the study were used for pilot-scale mirin production (50 kg). Ninety per cent of the untrained panelists accepted the quality of mirin produced at the above-mentioned conditions.